Haemodynamic study of idealistic renal artery under different flow conditions - Cherian, Johny; S. M., Abdul Khader; B., Raghuvir Pai; M., Zuber; K. A., Ahmed; Ahmad, Zanuldin (IOS Press, 2019)
Atherosclerosis is a condition of plaque/fatty deposit on the walls of the artery resulting in obstruction to blood flow. Several researchers have studied the hemodynamic behavior under resting condition on patient-specific models. The aim of present study is to investigate the hemodynamic behavior in 3D models of an idealistic abdominal aorta with renal branches based on (Computed Tomography) CT image. A new technique is used to develop the idealistic model from the single slice. Fluent solver in ANSYS is used to simulate both steady and transient flow of the normal idealistic abdominal aorta model. The investigation is focused on the flow field and Wall Shear Stress (WSS). The flow variable monitored at steady state analysis for Reynolds number 400 agrees well with selected time step in the transient analysis for the same outlet boundary conditions. The transient analysis is performed for both resting and exercise cases at constant pressure of 90 mmHg. Significant changes in flow recirculation and WSS has been demonstrated during rest and exercise condition. These observations agree well with the available literature.